A method to realize traceability in development processes. Issue 11 (November 2016) - Dreves, Rainer; Hällmayer, Frank; Haunert, Lutz; Sechser, Bernhard; Rieß, Armin
Abstract: The SoQrates Working Group "Traces" develops methods for documenting a continuous flow of information and takes into account the transparency of the activities of the different disciplines. Particularly, the level of detail, accuracy, and completeness of the interfaces are considered. These methods consider also the required traceability demanded by different standards. By using the developed methods, a platform development with reusable components is possible. In combination with an efficient variant management, existing components can be combined to new customer products in a very short time (design to market). The closed traceability approach increases quality and safety veritably without additional resources. This paper describes the current results of the SoQrates Working Group "Traces" as a method description with best practice examples of the participating companies and research institutions.